The Transmission of Western Dao to the East:An Architectural Study of Xiangya Hospital and Yali (Yale) University - LIU Yishi, (Journal of Research for Christianity in China (JRCC), 2025)
This paper traces the evolution of Western hospital architectural design concepts and methodologies, as well as their adaptation and implementation after being introduced to China. It focuses on Xiangya Hospital and Yale University, both established in the 1910s, examining the succession of their architectural design proposals and the construction processes involved.